PENELITIAN STRUKTUR GEOLOGI DAN KAITANNYA TERHADAP KEMUNGKINAN ADANYA POTENSI EMAS PRIMER DAERAH GUNUNG ASTANA BOGOR, JAWA BARAT - Haryanto, Iyan (Bulletin of Scientific Contribution, 2005)
The study area that is mainly hilly, contains volcanics matters such as breccias, tufaceous lapili, tufand lava. Several outcrops are followed by mineralization where quartz vein also occurred.Developed structures in the study area are quite complex, where NE – SW faults pairing with NW –SE faults. Mineralization zones and quartz vein are found on faults segments, these evidence shows thatthere are primary Au prospect at the subsurface in the study area.